Analysis of the Principle of Justice in Constitutional Court Decision Number 65/PUU-XXI/2023 on Campaigning in Educational Places and Government Facilities (Lex Journal : Kajian Hukum dan Keadilan, 2024)
As stated in Ruling Number 65/PUU-XXI/2023, the Constitutional Court's legal ratio for permitting campaigns in government buildings and educational institutions is to be examined in this study, together with the legal implications of the quo Constitutional Court ruling. This study employs a normative technique incorporating case, conceptual, and legislative approaches. According to the research findings, the Constitutional Court's decision to permit campaigns in government buildings and educational settings was made to ensure that the rules in Law No. 7 of 2017—specifically, Article 280 paragraph (1) letter h—do not conflict with the provisions in the Explanatory Chapter. In addition, the Court thinks that permitting campaigns in government buildings and educational institutions will promote political understanding, particularly among students. The legal analysis of the Constitutional Court ruling and associated election regulations reveals the necessity for more specific legal requirements to effectively govern campaign processes and concepts, such as Article 280 paragraph (1) letter h. The rules outlined in the explanatory chapter are not always followed by restrictive regulations as specified in the body because the Court should adopt a methodical and forward-looking (futuristic) interpretation.